The occupation of Belvoir by the Hospitallers - Damien Carraz (Medievalista)
What do we know about the occupation of the castle of Belvoir by the Hospitallers of St. John of Jerusalem? This paper endeavors to draw up the state of the written documentation, consisting of a few chronicles, both Arabic and Latin, supplemented by charters from the Hospital’s collections. The history of the castle is put into perspective with the process of militarization of the Order and its growing involvement in the defense of the Latin states of the East. Acquired between 1165 and 1168, Belvoir quickly played a key role in the defense of Galilee, to the point of appearing as a major fortress of the Hospital. By January 1189, however, the place was taken over by the Ayyūbids. In 1241, following a treaty with al-Kâmil, Sultan of Egypt, the castle and its territory were returned to the Hospitallers. However, we do not know the circumstances under which the brothers moved back into a castle that had, in the meantime, suffered several destructions. In 1255, the Order strengthened its position by absorbing the possessions of the monastery of Mount Tabor. But, between 1263 and 1266, the campaigns of the Sultan Baybars resulted in the destruction of the Hospitaller settlement in eastern Galilee.